KAJIAN KUALITAS AIR SUNGAI KARANG ANYAR PANTAI BERDASARKAN BIOINDIKATOR MAKROOBENTHOS - Encik Weliyadi; Imra Imra; Husein Husei; Bara Anugrah (Universitas Teuku Umar, 2020)
Macrozoobenthos are organism that can be used as bioindicators of water quality because of their population changes influenced by environmental factors. The research was conducted in the coastal flow area of Karang Anyar Pantai Tarakan City, because this area is suspected to be a source of pollutants with varying environment conditions. The purpose of research is to know the physical chemistry of the water-chemical physics area from Karang Anyar Pantai with the index diversity (H ) of macrozoobenthos as bioindicators. The Sampling methods was purposive sampling. Calculation of diversity index (H'), similarity (E), and Dominancy (D) use the Shannon-Wienner index. The variables measured include physics (temperature, brightness, current velocity, and turbidity) and chemistry (pH and DO). The results showed an abundance of macrozoobenthos ranging from 2045-4129 ind/m. The value of the Diversity index (H) of macrozoobenthos ranges from 0.19 to 0.24.Keywords: DAS Karang Anyar Pantai, diversity, Macrozoobentos